Statistical characteristics of MST radar echoes and its interpretation - Woodman Pollitt, Ronald Francisco (1989)
En: Middle Atmosphere Program. Handbook for map, volume 30 / Edited bt: S. Fukao. Capítulo de libro: p. 114-150.